Complementary and Alternative Medicine in Autism Spectrum Disorder: parents’ experience from a middle-income European country - Stojanovska, Irena; Trajkovski, Vladimir (Informa UK Limited, 2023)
Introduction: This study quantitatively evaluated the use and perceived efficacy of Complementary and Alternative Medicine (CAM) treatments among individuals with Autism Spectrum Disorder (ASD) in Macedonia, a middle-income country in Southeast Europe. Methods: A web-based survey was conducted among 103 parents of 103 individuals with ASD, and descriptive statistics and non-parametric tests were used to analyze the data. Results: For the purpose of this study, special diets and the other CAM treatments were analyzed separately. CAMs were used by 76% of the participants with ASD, while 29% were on a special diet. Over 90% of parents positively rated the efficacy of CAM and special diets. Higher parental education was associated with higher CAM use (p¼0.042). The age of the individual with ASD (p¼0.009), severity of ASD (p¼0.037), and co-occurring neurodevelopmental/neuropsychiatric disorders (p¼0.029) also influenced the use of CAMs and/or special diets. Around half of parents were not/were partially informed by their providers about the treatments they recommended. Conclusion: This study showed a high prevalence of use of CAM (somewhat lower of special diets) coupled with insufficient familiarity with the attributes of these treatments. Found to affect the use of CAM and/or special diets were the level of parental education, the age of the affected individual, severity of ASD, and the presence of co-occurring neurodevelopmental/neuropsychiatric disorders.
Keywords: Autism Spectrum Disorder; Complementary and Alternative Medicine; supplements; diet; Europe; middle-income country